1998
DOI: 10.1111/j.1600-051x.1998.tb02485.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of periodontal disease in a Swedish adult population 1973, 1983 and 1993

Abstract: The aim of this study was to compare changes in periodontal status in a Swedish population over a period of 20 years. Cross-sectional studies were carried out in Jönköping County in 1973, 1983, and 1993. Individuals were randomly selected from the following age groups: 20, 30, 40, 50, 60, and 70 years. A total of 600 individuals were examined in 1973, 597 in 1983, and 584 in 1993. The number of dentate individuals was 537 in 1973, 550 in 1983, and 552 in 1993. Based on clinical data and full mouth intra-oral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
1
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 28 publications
8
74
1
6
Order By: Relevance
“…This disagreement with our results, as discussed by Hugoson et al (16) may be possibly attributed to a decrease in chronic periodontitis due to a better oral hygiene. However beyond the term iatrogenia there is a wide range of factors which can be taken into account.…”
Section: Discussioncontrasting
confidence: 57%
“…This disagreement with our results, as discussed by Hugoson et al (16) may be possibly attributed to a decrease in chronic periodontitis due to a better oral hygiene. However beyond the term iatrogenia there is a wide range of factors which can be taken into account.…”
Section: Discussioncontrasting
confidence: 57%
“…Gingival hyperplasia is a relatively common periodontal complication in renal transplantation patients that has been attributed to cyclosporin dosage and the presence of dental plaques, likely contributing to gingival inflammation (50). Estimates of the prevalence of periodontitis vary across studies (Table 1): a 14% prevalence of moderate to severe periodontitis was reported among individuals Ͼ20 years of age in the United States population (51) and 13% of subjects had severe periodontitis in a normal Swedish population (52). This divergency in prevalence depends on methodological, etiological, agerelated, racial, ethnic, socioeconomic, cultural, and behavioral factors that may be specific for each country.…”
Section: Poor Oral Health As a Source Of Inflammationmentioning
confidence: 99%
“…1 Interest in risk assessment for these diseases came from the observation that periodontitis not only impairs the general state of health (loss of the teeth), but also appears to have a relationship with cardiovascular and cerebrovascular diseases. 2 There is evidence that the interindividual variability in this condition depends on environmental (poor hygiene of oral cavity, smoking etc) 3,4 and genetic factors, most of which are not yet identified.…”
Section: Introductionmentioning
confidence: 99%